Novelty Stress Increases Fecal Pellet Output in Mongolian Gerbils: Effects of Several Drugs - Shiho Okano; Hideaki Nagaya; Nobuhiro Inatomi (Elsevier, 2005)
Stress-induced colonic functional changes have been investigated mainly under conditions involving physical stress, like in the restraint stress model. In this study, we established a new stress-induced defecation model involving the placement of Mongolian gerbils in a novel environment (novelty stress) and determined the effects of several drugs on novelty stress-induced fecal pellet output. When animals kept in groups were placed individually in small cages, the fecal pellet output markedly increased, although the upper intestinal transit measured by charcoal method was not changed. The concentration of plasma adrenocorticotropic hormone was moderately but significantly increased by the novelty stress. Drugs reportedly effective for stress-induced defecation, like alosetron hydrochloride, atropine sulfate, and trimebutine maleate, inhibited both the novelty stress-induced increase in fecal pellet output and spontaneous defecation. In contrast, TAK-637, a tachykinin NK1-receptor antagonist, and diazepam inhibited the novelty stress induced defecation but did not inhibit spontaneous defecation. The present study indicated that novelty stress increases fecal pellet output without affecting the upper intestinal transit; this model may be useful for evaluating the effects of drugs on stress-stimulated colonic motility. Keywords:: novelty stress, defecation, intestinal transit, fecal pellet, irritable bowel syndrome